The Economic Development in the Context of the Development of Foreign Trade in Poland – a Comparison to some EU Countries - Anna Rytko (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The themes of the impact of foreign trade on economic growth has been repeatedly assumed by investigators and were most often related to various aspects: the openness of the economies, economic prosperity, competitiveness and diversification of export. The objective of the research was the evaluation of changes in economic development and the development of foreign trade in Poland comparing them with the EU and some EU countries. Particular attention was given to the issue of diversification and competitiveness of exports by putting the hypothesis that the greater product diversification of Polish export, the greater its competitiveness, which leads to economic growth. The work uses the following test methods: descriptive methods, statistical methods, the indexing methods of which Indicator of the Absolute Deviations and Revealed Comparative Advantages were calculated. Export diversification can lead to speeding up the pace of economic growth. By analyzing in detail the situations in Poland can conclude that it is advisable to diversify of the export structure.